2014
DOI: 10.1071/is13051
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics of Caribbean Micrathena (Araneae : Araneidae) suggests multiple colonisation events and single island endemism

Abstract: The terrestrial biota of the Caribbean islands includes many lineages, some whose presence on the islands dates back some 35–40 million years ago, when land bridges are thought to have linked islands to continents, and others that have colonised more recently via dispersal. The New World spiny orb-weavers (Micrathena Sundevall, 1833) are a diverse group of mostly Neotropical spiders. Eight species have been described on the Greater Antilles islands: three widespread and five single island endemics. Here, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 34 publications
7
48
3
Order By: Relevance
“…The intermediate dispersal model (Agnarsson et al 2014; Agnarsson and Kuntner 2012; Claramunt et al 2012; Diamond et al 1976) predicts that species richness across archipelagos peaks in intermediate dispersers but is comparatively low in excellent dispersers where oceanic barriers are less effective. Our findings are consistent with this model – Argiope spiders are effective dispersers and unlike most arachnid lineages studied in the Caribbean where single island endemism is prominent (Cosgrove et al 2016; Crews and Gillespie 2010; Dziki et al 2015; Esposito et al 2015; McHugh et al 2014) Argiope have undergone little diversification in the Caribbean. A similar pattern was found, for example, in some Selonops lineages in the Caribbean (Crews et al 2010) and in the nephilids of the western Indian Ocean islands.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The intermediate dispersal model (Agnarsson et al 2014; Agnarsson and Kuntner 2012; Claramunt et al 2012; Diamond et al 1976) predicts that species richness across archipelagos peaks in intermediate dispersers but is comparatively low in excellent dispersers where oceanic barriers are less effective. Our findings are consistent with this model – Argiope spiders are effective dispersers and unlike most arachnid lineages studied in the Caribbean where single island endemism is prominent (Cosgrove et al 2016; Crews and Gillespie 2010; Dziki et al 2015; Esposito et al 2015; McHugh et al 2014) Argiope have undergone little diversification in the Caribbean. A similar pattern was found, for example, in some Selonops lineages in the Caribbean (Crews et al 2010) and in the nephilids of the western Indian Ocean islands.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, specimens from Cuba were deeply divergent from the remaining areas in all analyses, which we take as evidence for discovery of a cryptic species here described as Argiope butchko sp. n. ‘Hidden’ taxonomic diversity in the Caribbean is being revealed in multiple lineages by the CarBio project (Cosgrove et al 2016; Dziki et al 2015; Esposito et al 2015; McHugh et al 2014) and future work aims to test taxonomic hypotheses in other ‘widespread’ arachnid species that range from excellent to relatively poor dispersers and thus test the intermediate dispersal model at various taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most biogeographic research in the Caribbean has focused primarily on vertebrates (Dávalos, ; Glor, Losos, & Larson, ; Hedges et al., ; Hrbek, Seckinger, & Meyer, ; Murphy & Collier, ; Říčan et al., ; Sato et al., ) and plants (Salzman & Judd, ; Santiago‐Valentin & Olmstead, ; Skean, ; Zona, ). There have been a few recent studies on invertebrates (Hall, Robbins, & Harvey, ; Matos‐Maraví et al., ; Morrone, ; Sourakov & Zakharov, ) including spiders (Crews & Gillespie, ; Dziki, Binford, Coddington, & Agnarsson, ; McHugh et al., ) and other arachnids (Cosgrove, Agnarsson, Harvey, & Binford, ; Esposito et al., ). These studies have found mixed support for vicariance (Chakrabarty, ; Dziki et al., ; Matos‐Maraví et al., ; Říčan et al., ) and dispersal (Crews & Gillespie, ; Glor et al., ; McHugh et al., ; Sato et al., ) depending on the biology and characteristics of each lineage.…”
Section: Introductionmentioning
confidence: 99%